2018
DOI: 10.15832/ankutbd.490966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Row Spacing on Yield, Yield Components and Crude Oil of Autumn and Spring Sowed Mustard (Sinapis arvensis L.) in Eight Locations of Turkey

Abstract: This study was conducted to evaluate the effect of autumn and spring sowing and row spacings (20, 30, 40, 50 and 60 cm) on yield, yield components and crude oil percentage of mustard (Sinapis arvensis L.) at eight locations lying in different ecological zones (Ankara,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…According to these results, different species of Brassica may possess important variations, in different sowing seasons and years and across locations, for plant height, plant branches, plant pods, thousand-seed weight, seed yield, and crude oil content due to differences in temperature, humidity, and precipitation, in agreement with Christensen et al (1985), Ilyasi et al (2018), and Kayaçetin et al (2018). During the present investigation the range of each parameter facilitated an understanding of the immediate extent of diversity among the genotypes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…According to these results, different species of Brassica may possess important variations, in different sowing seasons and years and across locations, for plant height, plant branches, plant pods, thousand-seed weight, seed yield, and crude oil content due to differences in temperature, humidity, and precipitation, in agreement with Christensen et al (1985), Ilyasi et al (2018), and Kayaçetin et al (2018). During the present investigation the range of each parameter facilitated an understanding of the immediate extent of diversity among the genotypes.…”
Section: Discussionsupporting
confidence: 73%
“…Each genotype was sown in a 3-rowed plot of 3 m in length with unreplicated row spacing of 30 cm (Kayaçetin et al, 2018). Utilizing 5 randomly selected plants, all genotypes were characterized as follows: days to emergence, days to 50% flowering, days to harvest, plant height, plant lateral branches, plant pods, thousand-seed weight, seed yield, and crude oil content.…”
Section: Field Experiments Observations and Data Analysismentioning
confidence: 99%
“…Winter cultivars are needed to obtain higher yields by cultivating these species. Kayacetin et al (2018a) and Kayacetin (2019) have shown that longer vegetative growth and shorter generative growth due to winter sowing contributes to higher yields compared to yield from summer sown crops. It has been determined that the B. juncea, B. rapa and B. nigra genotypes must be grown in winter (Figure 10 - Kayacetin, 2019).…”
Section: Possibilities Of Mustard Cultivation In Turkeymentioning
confidence: 99%
“…B. juncea surpassed B. rapa in yield tests and earlier maturity (Kayacetin, 2019). Kayacetin et al (2018a) and Kayacetin (2019) further suggest that B. juncea and B. rapa should be counted as the most promising species for biodiesel industry.…”
mentioning
confidence: 91%
See 1 more Smart Citation